2016
DOI: 10.1089/mdr.2015.0122
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Susceptibility to Cefepime in Clinical Isolates of Enterobacteriaceae Producing OXA-1 Beta-Lactamase

Abstract: An increase of Enterobacteriaceae isolates with reduced susceptibility to cefepime (FEP) and amoxicillin/clavulanate (AMC) has been observed in our area. The aim of this study was to characterize this antibiotic resistance phenotype and its molecular epidemiology. A total of 33 Enterobacteriaceae strains were studied. blaOXA-1 genes and their genetic environment were analyzed by polymerase chain reaction (PCR) and sequencing. Plasmids were transferred by conjugation and/or transformation and classified using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…The bla OXA-1 gene has been frequently found to be associated with genes encoding ESBL’s. This, along with the OmpK36 porin loss can cause reduced susceptibility to cefepime (Beceiro et al, 2011; Torres et al, 2016). bla OXA1 was found in the following genetic environment, IS26-catB4-bla OXA-1 -aac (6′)- Ib-cr-IS26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bla OXA-1 gene has been frequently found to be associated with genes encoding ESBL’s. This, along with the OmpK36 porin loss can cause reduced susceptibility to cefepime (Beceiro et al, 2011; Torres et al, 2016). bla OXA1 was found in the following genetic environment, IS26-catB4-bla OXA-1 -aac (6′)- Ib-cr-IS26 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the strainYMC2011/7/B774, this strain has bla CTX-M15 and bla OXA-1 along with the bla SHV-187 . Reduced susceptibility to cefepime is due to the bla OXA-1 (Torres et al, 2016). The presence of multiple aminoglycoside resistance genes such as aac (6′) Ib-cr , strA , strB , oqxA , oqxB and QnrB66 offered resistance to ciprofloxacin.…”
Section: Resultsmentioning
confidence: 99%
“…Madhan Sugumar [30] found that bla OX A-1 β-lactamase-producing strains were resistant to piperacillin/tazobactam (100%), levofloxacin (91.6%), amikacin (75%), cefoxitin (50%), ertapenem (25%), imipenem (16.6%) and meropenem (16.6%). Eva Torres [33] reported that reduced susceptibility to cefepime was mostly due to bla OXA-1 β-lactamase in E. coli. However, the relationship between the bla OXA-1 gene and carbapenems has never been reported.…”
Section: Rasmussen Et Al and Andres Opazo Et Almentioning
confidence: 99%
“…6 The OXA-ESBL type has been found more frequently in Pseudomonas aeruginosa, but with its genes distributed on plasmids; OXA are currently found in several members of the Enterobacteriaceae family too. 7,8 Despite worldwide distribution of ESBL, their epidemiology varies according to the geographic region. The enzymes of the CTX-M group currently overlap with other ESBL and have expanded beyond hospital borders.…”
Section: Introductionmentioning
confidence: 99%